Effect of Combined Application of ZA Fertilizer and Goldensoil G-03 Organic Powder Fertilizer on the Growth and Yield of Lumbu Putih Garlic (Allium sativum L.) - Krisna Wahyu Stianingsih; Makhziah Makhziah; Felicitas Deru Dewanti (The University of Lampung, 2026)
Garlic (Allium sativum L.) is a valuable horticultural crop in Indonesia, widely used both as a culinary staple and for its medicinal properties. This study was conducted from October 2024 to January 2025 in Paras Hamlet, Kembangbelor Village, Pacet District, Mojokerto Regency, East Java, to determine the optimal combination of ZA fertilizer and Goldensoil G-03 organic powder fertilizer (POP) for enhancing garlic growth and yield. The research employed a factorial design with two factors using a Split Plot Design (RPT) with three replications. The main plots consisted of ZA fertilizer applications at 200 kg/ha (Z1), 300 kg/ha (Z2), and 400 kg/ha (Z3), while the sub-plots included Goldensoil G-03 POP treatments: no POP (G0), 100 g/20 kg inorganic fertilizer (G1), 200 g/20 kg (G2), and 300 g/20 kg (G3). Data were analyzed using ANOVA and the HSD test at a 5% significance level. The research results showed that the independent application of 400 kg/ha ZA fertilizer had a significant effect on garlic growth and yield. However, the independent application of Goldensoil G-03 did not have a significant impact on garlic growth and yield.